An empirical analysis of the determinants of network construction for Azul Airlines. (June 2022) - Oliveira, Bruno F.; Oliveira, Alessandro V.M.
Abstract: This paper describes an econometric model of the Brazilian domestic carrier Azul Airlines' network construction. We employed a discrete-choice framework of airline route entry to examine the effects of the merger of another regional carrier, Trip Airlines, with Azul in 2012, especially on its entry decisions. The results suggest that post-merger, Azul has adopted a more idiosyncratic entry pattern, focusing on the regional flights segment to conquer many monopoly positions across the country, and strengthening its profitability without compromising its distinguished expansion pace in the industry.